Lives of the mind : the use and abuse of intelligence from Hegel to Wodehouse - Kimball, Roger, 1953- (Chicago : Ivan R. Dee, 2003)
"In Lives of the Mind, Roger Kimball, one of our most astute cultural critics, offers a delicious study of genius - and pseudo-genius - at work, and shows how intelligence can be used and abused." "When does a love of ideas become a dangerous infatuation? What antidotes are there for the silliness of unanchored intellect? Mr. Kimball ponders a wide range of figures, looking at their fidelity to the truth and their quotient of what he calls "spiritual prudence": their healthy contact with reality. Drawing on figures as various as Plutarch and Hegel, Kierkegaard and P.G. Wodehouse, Descartes and Trollope, Wittgenstein and Bertrand Russell, he takes the reader on a sharply observed tour of Western intellectual and artistic aspiration. He shows what happens when intellect trumps common sense, and how an affirmation of shared values and ordinary reality can rescue us from the temptations of the higher stupidity." "Because language is one of the primary theaters of intelligence, a large part of Lives of the Mind is devoted to savoring forms of verbal extravagance. "What I have assembled," Mr. Kimball writes, "is in part the scrapbook of an intellectual pathologist. But it is also worth noting that the heroes in this book rather outweigh the villains." If there is a moral to be drawn, it is an old and familiar one: on one side, the perils of intellectual infatuation; on another side, the virtues of modesty."--Jacket
Raymond Aron and the Power of Ideas -- Plutarch and the Issue of Character -- "Strange Seriousness": Discovering Daumier -- Walter Bagehot: The Greatest Victorian -- What's Left of Descartes? -- Schiller's "Education" -- Difficulty With Hegel -- Schopenhauer's Worlds -- What Did Kierkegaard Want? -- George Santayana -- Wittgenstein: The Philosophical Porcupine -- Bertrand Russell: Apostle of Disillusionment -- Who Was David Stove? -- Tocqueville Today -- Anthony Trollope: A Novelist Who Hunted the Fox -- G.C. Lichtenberg: A "Spy on Humanity" -- Genius of Wodehouse -- Mystery of Charles Peguy.
Includes bibliographical references and index.
Keywords: Philosophy, Modern; Philosophy, Modern